Creating Positive Environments in Skilled Nursing Facilities to Support Best Practice Implementation: An Overview and Practical Suggestions - Douglas, Natalie F.; Hickey, Ellen (Seminars in Speech and Language, 2015)
The purpose of this article is to discuss various types of organizational cultures and climates in relationship to best practice implementation. Although not specific to speech-language pathology, positive organizational cultures and climates are associated with better clinician and patient outcomes in health care services than dysfunctional and/or hierarchical organizational cultures and climates. A goal of this article is to help the practicing speech-language pathologist (SLP) promote positive culture change in the skilled nursing facility (SNF) setting. Recommendations to improve the organizational culture and climate of SNFs will be presented through practical examples of collaborative practice. Further suggestions will be surmised from the organizational psychology and interprofessional education literature. The connection between organizational culture and climate, interprofessional education, collaborative practice, and SLPs' best practice implementation in the SNF setting will be discussed. Avenues for future work are suggested.
Keywords: Implementation science; skilled nursing facilities; speech-language pathologists; organizational culture and climate; collaborative practice; interprofessional education; long-term care